2014
DOI: 10.1002/hbm.22466
|View full text |Cite
|
Sign up to set email alerts
|

Pupil diameter covaries with BOLD activity in human locus coeruleus

Abstract: The locus coeruleus-noradrenergic (LC-NA) neuromodulatory system has been implicated in a broad array of cognitive processes, yet scope for investigating this system's function in humans is currently limited by an absence of reliable non-invasive measures of LC activity. Although pupil diameter has been employed as a proxy measure of LC activity in numerous studies, empirical evidence for a relationship between the two is lacking. In the present study, we sought to rigorously probe the relationship between pup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

51
723
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 724 publications
(782 citation statements)
references
References 75 publications
51
723
8
Order By: Relevance
“…Critically, electrical activity in the monkey LC is closely associated with the moment to moment dilation of the pupil (Rajkowski, Kubiak, & Aston-Jones, 1993), and concurrently measured pupil diameter covaries with LC activation during both rest and the oddball decision task in human fMRI studies (Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014). Given the close association between the LC activity and the PD response in uncertainty.…”
Section: Neurobiology Of the Dilation Responsementioning
confidence: 99%
“…Critically, electrical activity in the monkey LC is closely associated with the moment to moment dilation of the pupil (Rajkowski, Kubiak, & Aston-Jones, 1993), and concurrently measured pupil diameter covaries with LC activation during both rest and the oddball decision task in human fMRI studies (Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014). Given the close association between the LC activity and the PD response in uncertainty.…”
Section: Neurobiology Of the Dilation Responsementioning
confidence: 99%
“…Activity of the PAG, a key midbrain structure involved in emotional processing and defensive motor behaviours (Blakemore et al, 2016;Satpute et al, 2013), was also modulated by subjective arousal. We note that our result might additionally reflect activity in the adjacent locus coereleus, as this structure is also implicated in mediating arousal (Murphy et al, 2014) and energizing behaviour (Varazzani et al, 2015). However, this remains speculative as our imaging parameters limit the ability to differentiate PAG activity from activity of surrounding brainstem nuclei (Satpute et al, 2013).…”
Section: Discussionmentioning
confidence: 89%
“…Converging evidence from fMRI and pupilometry measures -an indirect index of LC activation (Alnaes et al, 2014;Gilzenrat, Cohen, Rajkowski, & Aston-Jones, 2003;Gilzenrat et al, 2010;Jepma & Nieuwenhuis, 2011;Joshi et al, 2016;Murphy et al, 2014Murphy et al, , 2011bRajkowski, Kubiak, & Aston-Jones, 1993)-demonstrate a noradrenergic drive in the episodic memory enhancement observed during voluntary movement execution. Furthermore, this LC activation is functionally coupled with a memory target area, parahippocampal gyrus, suggesting a framework in which noradrenaline release triggered by voluntary movements engages memory target areas to promote episodic memory encoding.…”
Section: Voluntary Movements Enhances Episodic Memory Via a Noradrenementioning
confidence: 97%
“…In general they found that LC activity was higher just preceding pupil dilations compared with constrictions, implying that the pupil changes do not cause changes in LC activation, rather they reflect underlying changes in The first study in humans that detailed the interrelationship between performance dynamics on a widely used attentional task and pupil diameter as an indirect index of LC-NE system activity was performed by (Murphy et al, 2011). In a new set of experiments, the same authors have recently demonstrated a positive correlation between continuous pupil diameter and BOLD activity in a dorsal pontine cluster overlapping with the LC by simultaneously recording pupilometry and fMRI both at rest and during performance of a two-stimulus oddball task (Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, 2014). LC was localized via both neuromelaninsensitive structural imaging (Shibata et al, 2006) and a previously published LC atlas (Keren, Lozar, Harris, Morgan, & Eckert, 2009).…”
Section: Pupil Diameter As An Indirect Index Of Lc Activitymentioning
confidence: 99%
See 1 more Smart Citation